2021
DOI: 10.1007/s13399-021-02060-1
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing role of biochar in controlling soil erosion and considering future aspect of production using microwave pyrolysis process for the same

Abstract: Microwave-assisted pyrolysis (MAP) is considered as one of the improved biochar production options given its cost efficiency, efficient heat transfer and better-quality control. Researchers have observed that biochar can be considered as an alternative erosion control material due to its high porosity, surface area, and surface functional groups. However, as per the available literature, contradictions exist regarding some erosion control mechanisms of biochar with respect to water holding capacity (WHC), bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 175 publications
(213 reference statements)
0
3
0
Order By: Relevance
“…Nitrogen-fixing species (e.g., legumes) are sometimes used for hedgerows, and their practice is applied to crops as green manure to enhance nutrient recycling, which greatly reduces the need for commercial fertilizers [36,179,180]. In recent years, some amendments, such as biochar and polyacrylamide (PAM), have become research hotspots and have been adopted to reduce soil and water loss [104,[181][182][183][184][185]. However, these materials should be carefully used due to their negative effect under certain conditions.…”
Section: Increasing Coveragementioning
confidence: 99%
“…Nitrogen-fixing species (e.g., legumes) are sometimes used for hedgerows, and their practice is applied to crops as green manure to enhance nutrient recycling, which greatly reduces the need for commercial fertilizers [36,179,180]. In recent years, some amendments, such as biochar and polyacrylamide (PAM), have become research hotspots and have been adopted to reduce soil and water loss [104,[181][182][183][184][185]. However, these materials should be carefully used due to their negative effect under certain conditions.…”
Section: Increasing Coveragementioning
confidence: 99%
“…It is generally known that biochar amendment increases plant growth in soils with a pH below the optimum (Jeffery et al, 2017) and that this indirect plant growth mechanism may be expected to contribute to any potential reduction of soil erosion. Wani et al (2023) ascertained that the application of biochar reduced the rate of erosion by altering soil characteristics. The biochar application provides better soil characteristics by reducing bulk density and specific gravity, while at the same time increasing its porosity and organic matter content.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, it has also been observed that the use of biochar as a soil amendment is a novel and promising approach. It enhances soil quality for better water holding capacity (WHC), higher agricultural productivity, improves geoengineering works, and reduces environmental pollution and erosion [3,[26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%